(untitled) (Research, Society and Development, 2021)
Mental stress represents a public health problem and exercise can boost mental health improvement. However, athletes are not immune to mental health challenges, including the high physical demand of elite athletes can negatively influence mental health and cause stress. This relationship of mental stress and elite athletes is still not well understood in reading and receives little attention from researchers. Thus, a systematic review study was carried out with the objective of analyzing the existence and impacts of mental stress in elite athletes. In this review, the following descriptors were used: Stress, Psychological; Athletes; Mental Health; Mental Health Associations. The databases used were PubMed, Web of Science and Scopus in English with articles published in the last five years. After qualitative selection and synthesis, seven studies were included. It was found that mental stress is common in athletes even compared to non-athletes. In the included studies there was a predominance of young women in varied sports, mainly summer sports such as volleyball and athletics. Mental stress seems to be related to training load. Studies with larger samples are needed in different sports to check mental stress in elite athletes with greater methodological rigor.